PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMA PGRI 1 PADANG - Mardiah, Ainul; Haryono, Yulia; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was aimed at revealing the development of the studentsâ mathematics conceptual understanding and to know whether the mathematics conceptual understanding of the students taught by using Guided Note Taking active learning strategy was better than that of students taught by using conventional learning in class XI IPS of SMA PGRI 1 Padang. This was an experimental research which used random toward the subject design. Based on the result of data analysis, it was found that the mathematics conceptual understanding of the students improved from a meeting to next one. In addition, the result of t-test showed that the value of tcalculated (2,40) was bigger than ttable (1,675) in which Î± was 0,05. This result indicated that the mathematics conceptual understanding of the students taught by using Guided Note Taking active learning strategy was better than that of students taught by using conventional learning in class XI IPS of SMA PGRI 1 Padang.